Synthesis of the Novel Nanocatalyst of Pt3Mo Nanoalloys on Ti0.8W0.2O2 via Hydrothermal and Microwave-Assisted Polyol Process - Anh Tram Ngoc Mai; Nguyen Khanh Pham; Kim Ngan Thi Tran; Van Thi Thanh Ho (Universitas Gadjah Mada, 2022)
Direct methanol fuel cell (DMFC) attracts much attention due to its high abundance, environmental friendliness, and convenient transportation and storage. In this study, a novel catalyst of Pt3Mo alloy nanoparticles (NPs) on non-carbon Ti0.8W0.2O2 support was synthesized by microwave-assisted polyol process. The characteristic of Pt3Mo NPS/Ti0.8W0.2O2 catalyst was determined by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electronic microscopy (SEM), energy-dispersive X-ray (EDX), and Brunauer-Emmett-Teller (BET) method. Pt3Mo NPs had an average diameter of approximate 5.18 nm and were uniformly anchored on Ti0.8W0.2O2 surface. The ratio of Mo in the Pt3Mo alloy was consistent with the theoretical value, which supported the effectiveness of the synthesis method. In addition, Pt3Mo/Ti0.8W0.2O2 electrocatalysts exhibited higher CO-like tolerance in methanol oxidation reaction (MOR) than commercial electrocatalysts, excellent catalytic activity, and strong durability after 2000 cycles. The synergistic effect of Pt-Mo alloy, and the strong interaction between the bimetallic Pt-Mo alloy and the mesoporous Ti0.8W0.2O2 support, could weaken the Pt-CO bond. Besides, the high corrosion resistance and superior electrochemical durability of TiO2-based oxide also contribute to the excellent stability of Pt3Mo/Ti0.8W0.2O2 electrocatalyst in harsh electrochemical media. These results revealed that this material could be a potential catalyst in DMFC technology.